Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Keywords: breakdown; colonisation; leaves; river; shredders

Effects of Leaf Litter Species on Macroinvertebrate Colonization during Decomposition in a Portuguese Stream - Abelho, Manuela (International Review of Hydrobiology, 2008)
This study evaluated if there are differences in leaf breakdown and invertebrate colonization among tree species differing in quality (toughness), and which factors could influence these differences. Common alder leaves decomposed significantly faster then either sweet chestnut or Spanish oak (k values of –0.0332, –0.0108, and –0.0112, respectively) during the first 2 months. Shredder abundance was highest when leaf mass remaining was 50%, and the samples clustered in mixed groups of sampling dates and leaf species, suggesting that stage of decomposition was an important factor influencing shredder colonization. During the first two months of decomposition, the physicochemical characteristics of leaf litter and the interaction between leaf toughness and the occurrence of frequent spates seemed to be the main factors affecting leaf breakdown rates in the stream. (© 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: breakdown; colonisation; leaves; river; shredders

Growth of forest plants (pine and holm-oak) inoculated with rhizobacteria: relationship with microbial community structure and biological activity of its rhizosphere - Garcı́a, Jose A.Lucas; Domenech, Jezabel; Santamarı́a, Carmen; Camacho, Marı́a; Daza, Antonio; Mañero, F.Javier Gutierrez (Environmental and Experimental Botany, 2004)
Four bacterial strains showing in vitro metabolic capacities related to their plant growth-promoting action (plant growthpromoting rhizobacteria (PGPRs)) were studied in the growth of holm-oak (Quercus ilex ssp. Ballota) and pine (Pinus pinea) plants at a forest nursery before outplanting. All strains signiﬁcantly increased some of the parameters studied (stem length, neck diameter and shoot dry weight), although, neck root diameter showed the smallest increase in general. An interaction plant/bacterial strain was observed. Some strains speciﬁcally increased aerial parameters in both plant species, whereas other strains did so mainly in one plant species. Analyses of PLFAs and incorporation of thymidine and leucine suggest differences in the perturbation of microbial communities previously established and in the capacity of adaptation to the rhizosphere environment among the different strains
Keywords: colonisation; PGPR; Pinus pinea; plfas; Quercus ilex ssp. ballota; rhizosphere; thymidine leucine incorporation

Growth of forest plants (pine and holm-oak) inoculated with rhizobacteria: relationship with microbial community structure and biological activity of its rhizosphere - Garcı́a, Jose A. Lucas; Domenech, Jezabel; Santamarı́a, Carmen; Camacho, Marı́a; Daza, Antonio; Mañero, F. Javier Gutierrez (Environmental and Experimental Botany, 2004)
Four bacterial strains showing in vitro metabolic capacities related to their plant growth-promoting action (plant growthpromoting rhizobacteria (PGPRs)) were studied in the growth of holm-oak (Quercus ilex ssp. Ballota) and pine (Pinus pinea) plants at a forest nursery before outplanting. All strains signiﬁcantly increased some of the parameters studied (stem length, neck diameter and shoot dry weight), although, neck root diameter showed the smallest increase in general. An interaction plant/bacterial strain was observed. Some strains speciﬁcally increased aerial parameters in both plant species, whereas other strains did so mainly in one plant species. Analyses of PLFAs and incorporation of thymidine and leucine suggest differences in the perturbation of microbial communities previously established and in the capacity of adaptation to the rhizosphere environment among the different strains
Keywords: colonisation; PGPR; Pinus pinea; plfas; Quercus ilex ssp. ballota; rhizosphere; thymidine leucine incorporation